PENGARUH MEDIA FUZZY FELT TERHADAP KOSAKATA ANAK USIA 5-6 TAHUN DI TK AL- HIDAYAH JAMBI - Intan Nurjannah; Hendra Sofyan; Akhmad Fikri Rosyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low vocabulary skills of 5–6-year-old children at Al-Hidayah Kindergarten in Jambi, as evidenced by the children’s limited ability to express ideas, answer questions, and convey information clearly. In fact, vocabulary mastery is a crucial foundation for children’s language development, influencing their communication skills, cognitive abilities, and academic readiness. One approach to improving children’s vocabulary skills is through the use of interactive and engaging learning media, such as fuzzy felt. This study aims to determine the effect of using fuzzy felt media on the vocabulary skills of 5–6-year-old children at Al-Hidayah Kindergarten in Jambi. This is a quantitative study using an experimental method with a one-group pretest-posttest design. The study subjects consisted of 12 children aged 5–6 years. Data collection was conducted through observation. The data were analyzed using a paired samples t-test. The results of the study indicate that there was an improvement in the children’s vocabulary skills after they were exposed to the fuzzy felt medium. This is evidenced by a mean difference of –11.583, indicating that the posttest scores were higher than the pretest scores. A significance value of 0.000 (Sig. < 0.05) indicates a significant difference between the pretest and posttest results. Therefore, it can be concluded that the use of fuzzy felt media significantly influences the improvement in vocabulary skills of 5–6-year-old children at Al-Hidayah Kindergarten in Jambi.